Effect of graphite dopant polyvinylidene fluoride (PVDF) electrospun composites - Mohd Saad, Muhammad Zamzuri; Syed Bakar, Sharifah Shahnaz; Yahud, Shuhaida; Idris, Muhammad Asri; Samat, Noorasikin (Universiti Malaysia Perlis, 2024)
Polyvinylidene Fluoride (PVDF) is a high purity thermoplastic fluoropolymer that has huge potential, has been employed in numerous electronics, space, and aeronautics industries.The beta-phase of PVDF is the most beneficial due to its superior piezoelectric and pyroelectric properties, which are essential for high-performance applications.Thus, the research on attaining the beta-phase has been critical. PVDF crystallinity could be enhanced by varying processing methods and parameters, including electrospinning. Various researchers have reported on the electrospinning PVDF as a successful route to get beta-phase. The morphology, crystalline phases, and electrical conductivity of PVDF fiber are significantly influenced by electrospinning parameters. In this work, the effect of graphite loading in PVDF is one of the parameters examined. The objective of this work is to investigate the impact of graphite dopantloading on the electrical conductivity of electrospun PVDF composite. The most straightforward and affordable way to create PVDF fibers isbyelectrospinning. PVDF was first dissolved using N, N-Dimethylformamide (DMF) before mixing with graphite (0.25wt%, 0.50wt%, 0.75wt%, and 1.0wt%). Each solution was then electrospinned to produceconductivecomposite fiber. The parameters werefixed at 25 kV voltage; 1.5ml/h flow rate; and 12cm tip-to-collector distance. The morphology, electrical conductivity, and crystalline phases of electrospun PVDF fibers were examined using scanning electron microscope (SEM), four-point probe and X-ray diffraction (XRD) machine. As the graphite concentration rises, SEM micrograph showed that more beads weredeveloped along with fiber sizes increment. Short electrospinning times result in insufficient electrospun mat thickness, which affects peak shift, according to XRD examination of all fibers. According to the results of the four-point probe examination, the conductivity rises dramatically and the resistance decreases as the graphite concentration increases